Functional roles of Na+/K+-ATPase in active ammonia excretion and seawater acclimation in the giant mudskipper, Periophthalmodon schlosseri - Chew, Shit F.; Hiong, Kum C.; Lam, Sock P.; Ong, Seow W.; Wee, Wei L.; Wong, Wai P.; Ip, Yuen K. (Frontiers in Physiology, 2014)
The giant mudskipper, Periophthalmodon schlosseri, is an amphibious fish that builds burrows in the mudflats. It can actively excrete ammonia through its gills, and tolerate high environmental ammonia. This study aimed to examine the effects of seawater (salinity 30; SW) acclimation and/or environmental ammonia exposure on the kinetic properties of Na+/K+-ATPase (Nka) from, and mRNA expression and protein abundance of nka/Nka α–subunit isoforms in, the gills of P. schlosseri pre-acclimated to slightly brackish water (salinity 3; SBW). Our results revealed that the Nka from the gills of P. schlosseri pre-acclimated to SBW for 2 wk had substantially higher affinity to (or lower Km for) K+ than NH4+, and its affinity to NH4+ decreased significantly after 6-d exposure to 75 mmol l-1 NH4Cl in SBW. Hence, Nka transported K+ selectively to maintain intracellular K+ homeostasis, instead of transporting NH4+ from the blood into ionocytes during active NH4+ excretion as previously suggested. Two nkaα isoforms, nkaα1 and nkaα3, were cloned and sequenced from the gills of P. schlosseri. Their deduced amino acid sequences had K+ binding sites identical to that of Nkaα1c from Anabas testudineus, indicating that they could effectively differentiate K+ from NH4+. Six days of exposure to 75 mmol l-1 NH4Cl in SBW, or to SW with or without 50 mmol l-1 NH4Cl led to significant increases in Nka activities in the gills of P. schlosseri. However, a significant increase in the comprehensive Nkaα protein abundance was observed only in the gills of fish exposed to 50 mmol l-1 NH4Cl in SW. Hence, post-translational modification could be an important activity modulator of branchial Nka in P. schlosseri. The fast modulation of Nka activity and concurrent expressions of two branchial nkaα isoforms could in part contribute to the ability of P. schlosseri to survive abrupt transfer between SBW and SW or abrupt exposure to ammonia.